Complex Model of Risk Assessment of Industrial Processes Mopori - Katarina Holla; Katarina Kampova; Andrea Peterkova; Andrew Collins (Communications - Scientific letters of the University of Zilina, 2013)
Modern day society wants to create optimal living conditions for its citizens and to ensure constant sustainable development. This objective cannot be achieved without reaching the required level of perceived security in complex. One of the areas that threaten the lives and property of people and are harmful for the environment is the anthropogenic crisis phenomena, which also include industrial accidents. Prevention of these accidents and subsequent reaction are the key issues considering adjustment of the level of security not only for the citizens of Slovakia, the European Union but also worldwide. The article focuses on the problem of prevention and the way how to deal with the issue in the Slovak Republicas well as on the fulfilment of the requirements in this field which emerge from our membership in the EU. The Faculty of Special Engineering at the University of Zilina deals with partial issues which are necessary to be solved by the approved project APVV – 10 Complex model of risk assessment of industrial processes. Partial results of the project, which is in the second year of its solution, are listed in the text below.